Influence of Hedgehog signaling pathway activation on calvarial defect healing in type I diabetic mice - WU Yingzhang, LIU Linan, LIU Shibo, HU Pei, LUO En (Kou qiang ji bing fang zhi = Journal of prevention and treatment for stomatological diseases, 2025)
Objective This study aimed to elucidate the mechanisms underlying the impaired bone healing capacity in type 1 diabetes (T1DM) by investigating the role of the Hedgehog (Hh) signaling pathway in the impaired healing of cranial defects caused by T1DM. Methods This study was approved by the experimental animal ethics committee of our hospital. A cranial defect model was established using Akita transgenic mice with spontaneous type I diabetes. The impact of T1DM on osteogenic differentiation and the Hh signaling pathway during cranial defect healing was explored by MicroCT scanning and immunohistochemical (IHC) analysis of osteocalcin (Ocn), Indian Hedgehog (Ihh), Patched1 (Ptch1), and zinc finger protein GLI1 (Gli1). Subsequently, the Hh signaling pathway was activated using smoothened agonist (SAG) (10 mg/kg, gavage), and its potential to improve cranial defect healing in T1DM was assessed by MicroCT and IHC staining. Finally, the ability of SAG (1 000 nmol/L) to counteract the inhibitory effects of a high-glu